Effect of N-butylscopolamine on intestinal uptake of fluorine-18-fluorodeoxyglucose in PET imaging of the abdomen - Stahl, A.; Weber, W. A.; Avril, N.; Schwaiger, M. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: Circumscribed or diffuse intestinal uptake of F-l 8-fluorodeoxyglucose (FDG) is a frequent finding in PET imaging of the abdomen often interfering with correct scan interpretation. The aim of the present study was to determine whether the antiperistaltic agent N-butylscopolamine reduces intestinal FDG-uptake. Methods: Whole body scans from 40 patients with malignant lymphoma and no evidence for intraabdominal tumor involvement were analyzed (6 bed positions; scan start 60 min post injection of approximately 350 MBq FDG; emission time 9 min per position; no attenuation correction). Twenty patients received 20 mg N-butylscopolamine in combination with an intravenous injection of FDG (test group) and 20 patients received only FDG (control group). For analysis, the intensity of bowel loops and diffuse abdominal background were compared to normal liver on a 4 point scale (0 = lowest intensity, 3 = highest) by two experienced nuclear medicine physicians. Furthermore, focal intestinal uptake was evaluated quantitatively by a R0I technique and bowel to liver ratios (b/l) were calculated. Results: Bowel loops had lower intensity and occupied less abdominal regions in the test group than in the control group (visual score 1 vs. 1.5, p = 0.01; abdominal regions 1 of 5 vs. 2.5 of 5, p = 0.04). The visual score for diffuse abdominal background was 0.5 in the test group and 1 in the control group (p = 0.04). Bowel uptake interfered with scan interpretation in 1 of 20 patients in the test group and 6 of 20 patients in the control group (p = 0.01 ). The b/l ratios were 1.5 ± 0.7 in the test group and 2.3 ± 1.4 in the control group (p = 0.08). Conclusion: Administration of N-butylscopolamine reduces intestinal uptake of FDG and may facilitate accurate interpretation of abdominal FDG-PET studies.
Keywords: Fluorine-l 8-fluorodeoxyglucose (FDG); positron emission tomography (PET); N-butylscopolamine; intestine; abdominal PET